Genetic polymorphisms in low-dose methotrexate transporters: current relevance as methotrexate therapeutic outcome biomarkers. (September 2014) - Lima, Aurea; Sousa, Hugo; Monteiro, Joaquim; Azevedo, Rita; Medeiros, Rui; Seabra, Vitor
Methotrexate (MTX) is used in low doses to treat a variety of diseases. Although the mechanism responsible for its therapeutic action is unknown, MTX membrane transport proteins (influx and/or efflux) can be major determinants of pharmacokinetics, adverse drug reactions and clinical response profiles. With progess in pharmacogenomics, the improvement of the prediction of patients' therapeutic outcome treated with low doses of MTX will offer a powerful tool for the translation of transporter SNPs into clinical practice and will be essential to sustain a breakthrough in the field of personalized medicine. Therefore, this paper provides an update on the current data on SNPs in genes encoding low-dose MTX membrane transport proteins and their relevance as possible biomarkers of MTX therapeutic outcome.